The theory and practice of bond portfolio management - Bernstein, Peter L. (New York : Institutional Investor Books, 1977)
The book examines bond portfolio, and the techniques of bond management. It also considers how to balance risk and return in bond portfolio so as to increase its efficiency in marketplace.
Includes bibliographical references
usc 12/02/2019
Loans
Keywords: Bonds